Understanding the Uniqueness of 2p Elements in Periodic Tables. Issue 67 (16th November 2020) - Wang, Zhen‐Ling; Hu, Han‐Shi; von Szentpály, László; Stoll, Hermann; Fritzsche, Stephan; Pyykkö, Pekka; Schwarz, W. H. Eugen; Li, Jun
Abstract: The Periodic Table, and the unique chemical behavior of the first element in a column (group), were discovered simultaneously one and a half centuries ago. Half a century ago, this unique chemistry of the light homologs was correlated to the then available atomic orbital (AO) radii. The radially nodeless 1s, 2p, 3d, 4f valence AOs are particularly compact. The similarity of r (2s)≈ r (2p) leads to pronounced sp‐hybrid bonding of the light p‐block elements, whereas the heavier p elements with n ≥3 exhibit r ( n s) ≪ r ( n p) of approximately −20 to −30 % . Herein, a comprehensive physical explanation is presented in terms of kinetic radial and angular, as well as potential nuclear‐attraction and electron‐screening effects. For hydrogen‐like atoms and all inner shells of the heavy atoms, r (2s) ≫ r (2p) by +20 to +30 %, whereas r (3s)≳ r (3p) ≳ r (3d), since in Coulomb potentials radial motion is more radial orbital expanding than angular motion. However, the screening of nuclear attraction by inner core shells is more efficient for s than for p valence shells. The uniqueness of the 2p AO is explained by this differential shielding. Thereby, the present work paves the way for future physical explanations of the 3d, 4f, and 5g cases. Abstract : 2p or not 2p? Similarity of radii (and energies) of the atomic valence orbitals is the precondition for hybridization and hybrid bonding. In the Coulomb potential of H‐like atoms, the 2p orbital without a radial node is much smaller than 2s (2s≫ 2p), whereas higher p orbitals are comparably less contracted ( n s≳ n p). The screening of nuclear attraction by the core shells is more effective for the core penetrating s orbitals, so that for the valence orbital radii of ordinary many‐electron atoms of the 2nd row, 2s≈2p, whereas in rows n >2, hybridization is less pronounced owing, i.a., to n s≪ n p.